Clinical and virologic factors associated with outcomes of COVID‐19 before and after vaccination among Veterans: Retrospective analysis from six New England states. Issue 7 (6th June 2022) - Lee, Megan; Cosentino, Danielle; Kyriakides, Tassos C.; Cavallaro, Tricia; Stack, Gary; Gupta, Shaili
Abstract: We aimed to characterize clinical and demographic factors affecting clinical outcomes of COVID‐19 and describe viral epidemiology among unvaccinated Veterans in New England. Veterans infected with COVID‐19 in Veterans Administration healthcare systems in six New England states from April 8, 2020, to September 2, 2021, were correlated with outcomes of 30‐day mortality, nonpsychiatric hospitalization, and intensive care unit admission (ICU‐care). We sequenced 827 viral genomes. Of 3950 Veterans with COVID‐19 before full vaccination, 81% were White, 8% were women, and the mean age was 60 years. Overall, 19% of Veterans required hospitalization, 2.8% required ICU care, and 4.9% died. In this largely male and older cohort, poor outcomes correlated with increasing age. Most New England Veterans (>97%) were infected with B.1 sublineages with the D614G mutation in 2020 and early 2021. B.1.617.2 lineage (68%) predominated after July 2021.